Philip Wager diary - Wager, Philip, 1790-1835.
Diary (102 pages), 1812 March 24-1814 April 12, kept by Wager while serving with the 12th U.S. Army Infantry Regiment at Lake Erie during the War of 1812.
Microfilm edition available
Microfilm produced from the original in the Manuscript Division.
Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- Army -- History -- War of 1812.; United States. -- Army. -- Infantry Regiment, 12th.; Erie, Lake -- History; United States -- History -- War of 1812.; Army officers